(untitled) (Research, Society and Development, 2022)
Objective: to analyze compliance with the criteria of the Baby-Friendly Hospital Initiative in the periods before and during the COVID-19 pandemic. Method: quantitative study with 12 Baby-Friendly Hospitals in Paraná. Secondary data from 2019 and 2020, available in the monitoring system of the Baby-Friendly Hospital Initiative, were used, with analysis of association with the Yule Coefficient. Results: 156 items were analyzed, of which 25 presented changes, of which 12 were fulfilled in 2019 and not fulfilled in 2020, and 13 were not and were now fulfilled. There was a slightly positive impact of the COVID-19 pandemic on the fulfillment of Steps 1, 2, 7 and 8, and a negative impact on Steps 3, 5 and 9. Conclusion: This scenario raises a design of measures to protect and encourage breastfeeding by institutions, professionals and health managers in order to develop strategies to support and provide maternal and childcare in accordance with public health policies.